Preparation and interaction study between fullerene and graphene in a polymeric matrix. (6th April 2015) - Alzari, Valeria; Zaragoza-Galán, Gerardo; Nuvoli, Daniele; Illescas, Javier; Rivera, Ernesto; Sanna, Vanna; Conca, Erika; Mariani, Alberto
Abstract: Defect-free graphene is easily obtained by the liquid dispersion method, without any chemical manipulation. Tetraethylene glycol diacrylate (TEGDA) is used as liquid medium in which the above nanofiller is dispersed alone or together with fullerene C60. TEGDA is used because of its good dispersion properties and as a monomer to be eventually polymerized, thus directly obtaining the corresponding polymer nanocomposites. Polymerization is performed by using both the classical or the frontal polymerization, Moreover, polymeric films were also prepared. The interaction between the two fillers and the influence of the synthetic techniques on material properties are deeply studied. The optical properties of the obtained nanocomposites are analyzed by absorption and fluorescence spectroscopy. Graphene containing materials show absorption at ca. 280 nm and exhibited significant emission in the range between 600 and 800 nm. In contrast, fullerene containing materials do not show any fluorescence, which can be attributed to a charge transfer phenomenon from graphene to fullerene C60.